PERLINDUNGAN PEMBAYARAN UPAH PEKERJA PASCA PUTUSAN MAHKAMAH KONSTITUSI NO. 100/PUU-X/2012 TENTANG UJI MATERIAL UU NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Dede Agus Agus (Fakultas Hukum, Universitas Samudra, 2020)
Employers may be protected from the obligation to pay wages and any payments arising from employment if it has expired two year since the inception of the right. This is unfair to workers (harm), then judicial review an article 96 of Law No.13 of 2003 on Manpower to Constitution by the Constitutional Court Decision Number 100 / PUU-X / 2012. Therefore, this paper is aimed to discuss the protection of wage payment of workers post-judicial review. This research method, normative juridical based on the secondary data and the statute approach, conceptual approach, case approach and qualitative descriptive analysis. The results showed that the Post-Decision of the Constitutional Court payment of wages of workers has been protected, this is no expiry in the payment of wages and other benefits. The Constitutional Court declares that Article 96 of Law No.13 of 2003 is contradictory to the Constitution, and has no binding force. The Constitutional Court's verdict provides legal certainty that wages and any payments arising from employment relationships may at any time be prosecuted if they have not been fulfilled, but on the other hand it creates legal uncertainty, since the expiration institution is created by law in the context of legal certainty.